The cozy book - Hoberman, Mary Ann.; Chen, Tony. (New York : Viking Press, 1982)
Verses relate a variety of foods, activities, smells, sounds, words, places, people, feeling, and other things perceived as being cozy.
School Library Journal
3.3
K-3
Keywords: Children's poetry, American; American poetry; American poetry